Schizophrenia and the use of alcohol and other drugs: epidemiological profile - Jássia Lopes Freitas da Silveira; Roberto Lazzarini de Oliveira; Bárbara Magalhães Viola; Thaís Marques da Silva; Richardson Miranda Machado (Universidade Federal do Ceará, 2014)
This study aimed at characterizing the social demographic and clinical profile of patients with schizophrenia and alcohol and other drugs addiction of a Center of Psychosocial Attention III of the Central-Western region of the State of Minas Gerais, Brazil, from July 1st, 1997 to July 1st, 2013. It is a descriptive, observational and retrospective epidemiological study. The sample consisted of 1618 patients and the main results were: prevalence of male patients (60.4%) and the age range was 21 - 30 years old (48.2%), presented more expressive abuse of alcohol (35.6%) and cannabinoids (29.5%) and the most frequent diagnosis of paranoid schizophrenia (41.7%). Understanding the factors associated to the coexistence of both conditions can provide a basis for the creation of interventional strategies to improve the prognosis of these patients.